Survey of in vitro fertilization add-ons in Japan (Izanami project) - Shionoya, N.; Yamada, M.; Harada, S.; Shirasawa, H.; Jwa, S. Chik; Kuroda, K.; Harada, M.; Osuga, Y. (Frontiers in Endocrinology, 2024)
Objective To identify any correlations between evidence levels, adoption rates, and additional costs of in vitro fertilization (IVF) add-ons. Design Online survey. Subjects The survey was conducted in 621 assisted reproductive technology-registered facilities that are members of the Japanese Society of Obstetrics and Gynecology from December 22, 2021, to February 13, 2022. Exposure The survey included details regarding the specific add-on modalities employed and their associated costs; inquiries pertained to the fertility healthcare infrastructure in Japan before the implementation of the National Health Insurance scheme. Main outcome measures The correlation between the adoption rate and cost of IVF add-ons and their evidence levels were analyzed. The evidence level of the add-on treatments was classified into Green, Amber, and Red categories based on the United Kingdom’s Human Fertilisation and Embryology Authority and Cochrane systematic reviews. Results A total of 438 eligible responses were analyzed, with clinics constituting 70.9% of the respondents’ facilities. A total of 18 add-ons were assessed, and 96.5% (423/438) of facilities used at least one add-on. A positive correlation of the adoption rate and an inverse correlation of the cost with the evidence level of the IVF add-on treatment were observed (not significant). Outpatient clinics, defined as medical facilities with no beds, had a significantly higher adoption rate (Amber, 65.7%; Red, 52.0%) of add-ons than other facilities, regardless of the evidence rating, although the costs were similar across all site attributes. Conclusion Accumulating evidence on the efficacy and safety of add-ons will lead to the development of medical care with a high-cost benefit, as an increase in the adoption rate and a decrease in cost are expected when limiting to medical care with a high level of evidence.